2022
DOI: 10.3390/foods12010093
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Wholemeal Rye Bread with Plant Sterols: Rheological Analysis, Optimization of the Production, Nutritional Profile and Starch Digestibility

Abstract: Bread is one of the staple foods of many countries, and its enrichment with bioactive compounds is trending. This phenomenon is focused on breads with a good nutritional profile, such as wholemeal rye bread (WRB), in which enrichment with plant sterols (PSs) is allowed in accordance with European regulations. The objective of the present study was to optimize the production of a WRB enriched with PS (PS-WRB) and to evaluate the proximate composition and starch digestibility as an indicator of nutritional quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The highest content of sugars was recorded for MRF, and the lowest was recorded for T530. The commercial wholemeal rye flour analyzed by Makran et al [ 23 ] was characterized by higher moisture, carbohydrate, and dietary fiber contents, a much lower protein content, a lower fat content, and an identical ash content than the MRF analyzed in our studies. In our study, MBF was characterized by lower moisture, fat, ash, and carbohydrate contents, and a higher protein content than wholegrain barley flour obtained in the laboratory by Hussein et al [ 24 ].…”
Section: Resultsmentioning
confidence: 53%
“…The highest content of sugars was recorded for MRF, and the lowest was recorded for T530. The commercial wholemeal rye flour analyzed by Makran et al [ 23 ] was characterized by higher moisture, carbohydrate, and dietary fiber contents, a much lower protein content, a lower fat content, and an identical ash content than the MRF analyzed in our studies. In our study, MBF was characterized by lower moisture, fat, ash, and carbohydrate contents, and a higher protein content than wholegrain barley flour obtained in the laboratory by Hussein et al [ 24 ].…”
Section: Resultsmentioning
confidence: 53%
“…Abbreviations: RAG, rapidly available glucose (RAG); RDS, rapidly digestible starch; SDS, slowly digestible starch; SHI, starch hydrolysis index production caused a decrease in the amount of RDS and an increase in the amount of SDS as well as a reduction in SHI values (Cingöz et al, 2022). Studies reported that the addition of oat bran and oat beta-glucan decreased the in vitro GI (Hu et al, 2022) and the addition of small millet flour (Sharma & Gujral, 2019) and plant sterols (Makran et al, 2022) increased the slow digestible starch content of breads. The study about the effects of soluble and insoluble dietary fiber additions on the digestion rate of starch reported that as the soluble dietary fiber content in the samples increased, the amount of RDS decreased and the amount of SDS increased (Oh et al, 2014).…”
Section: Notementioning
confidence: 99%
“…The PS-WRB optimized baking procedure and the chemical composition (% w/w, dry basis) are as stated in Makran et al [4] (protein: 7.8 ± 0.1; ash: 2.0 ± 0.1; lipid: 4.7 ± 0.2; carbohydrate: 65.2 ± 0.6; insoluble fiber: 15.2 ± 1.8; soluble fiber: 5.1 ± 0.2). For the human oral phase, three portions of PS-WRB (81.45 ± 1.14 g) were chewed as described in Faubel et al [10] to obtain the respective oral bolus.…”
Section: Sample and Oral Phase Digestionmentioning
confidence: 99%
“…These metabolites play crucial roles in promoting gut integrity and regulating glucose homeostasis, lipid metabolism, appetite, immune system, and inflammatory response [3]. Fiber-rich food (such as wholemeal rye bread with 15.3 g of fiber/100 g of bread [4]) selectively promotes the growth of Bifidobacterium, a specific acetate-and butyrate-producing bacteria [5], as well as Lactobacillus [6].…”
Section: Introductionmentioning
confidence: 99%